Implantable cardioverter defibrillators: risks accompany the life-saving benefits. Issue 10 (15th March 2012) - Atwater, Brett D; Daubert, James P
Abstract : Sudden cardiac arrest is the one of the most common causes of death in developed countries and accounts for between 180 000 and over 450 000 per year in the USA. Antiarrhythmic drug approaches to prevention of sudden cardiac death have been resoundingly ineffective. The implantable cardioverter defibrillator (ICD) constitutes one of the most important and well validated therapeutic advances in modern cardiovascular medicine. Consequently, ICD use has increased exponentially, although implementation has been quite variable geographically and with respect to other measures. In view of the expanded use of ICDs, the potential shortcomings and risks of ICD therapy have attracted attention. This commentary summarises the weaknesses, disadvantages and risks of the ICD in a balanced fashion in light of their proven life-saving benefits.